Selection of optimal culture conditions for expression of recombinant beta-glucosidase in Escherichia coli - Thi Binh, Nguyen; Thi Quy, Nguyen; Thi Huyen, Do; Thu Hong, Le Thi; Nam Hai, Truong (Vietnam Journal of Biotechnology, 2022)
Beta-glucosidase (BGL) is an enzyme involved in the hydrolysis of cellulose and plays an important role in many biological processes. This enzyme is widely available in animals, plants, and microorganisms. Expression of the recombinant enzyme in Escherichia coli is considered a suitable choice for high production via a fast growth rate and feasible manipulation. In this study, we optimised some conditions for the high soluble production of recombinant beta-glucosidase whose gene sequence was mined from the DNA metagenome of Cuc Phuong humus surrounding white rot fungi. The gene bgl was cloned in pET 22b(+) and expressed in the E. coli Rosetta 1 strain. Production of the recombinant BGL was examined at temperature ranges from 18 to 37oC. The recombinant BGL was obtained as a soluble form at low temperatures, and the optimal temperature was 25°C. In comparison to LB, TB, SB, PE media, mTB rich medium in presence of glucose produced the most BGL. Besides, the results assessing the inducer condition showed that the best IPTG concentration for producing the BGL was 0.3 mM IPTG. Furthermore, some fermentation conditions affecting the level of BGL production were assessed as the induction point and harvesting time. The BGL production was the most suitable when the cell at mid-log phase with an OD600 1 and harvesting time after 4 hours of induction. Importantly, the recombinant BGL had good activity on the esculin substrate plate. Based on the selected conditions, the recombinant BGL could be produced high amount to facilitate for future purification and characterization of the recombinant BGL.